Urinary β2-Microglobulin Is a Good Indicator of Proximal Tubule Injury: A Correlative Study with Renal Biopsies. (20th November 2014) - Zeng, Xu; Hossain, Deloar; Bostwick, David G.; Herrera, Guillermo A.; Zhang, Ping L.
Abstract : Objective . After filtration through glomeruli, β 2-microglobulin is reabsorbed in proximal tubules. Increased urinary β 2-microglobulin indicates proximal tubule injury and measurement of β 2-microglobulin in urine is useful to determine the source of renal injury. Kidney injury molecule-1 (KIM-1) has been characterized as a selective proximal tubule injury marker. This study was designed to evaluate the correlation of urinary β 2-microglobulin concentration and KIM-1 expression as evidence of proximal tubule injury. Methods . Between 2009 and 2012, 46 patients with urine β 2-microglobulin (RenalVysion) had follow-up kidney biopsy. Diagnoses included glomerular and tubule-interstitial disease. Immunohistochemical staining for KIM-1 was performed and the intensity was graded from 0 to 3+. Linear regression analysis was applied to correlate the values of urinary β 2-microglobulin and KIM-1 staining scores. P < 0.05 was considered statistically significant. Results . Thirty patients had elevated urinary β 2-microglobulin. KIM-1 staining was positive in 35 kidney biopsies. There was a significant correlation between urinary β 2-microglobulin and KIM-1 staining ( P < 0.05). Sensitivity was 86.6%, specificity was 43.7%, positive predictive value was 74.2%, and negative predictive value was 63.6%. Conclusion . Increased urinary β 2-microglobulin is significantly correlated with KIM-1 staining in injured proximal tubules. Measurement of urine β 2-microglobulin is a sensitive assay for proximal tubule injury.